Effect of Drug Abuse on Juvenile Delinquency: A Case Study Kabale Municipality. - Mutabazi, Dickson (Kabale University, 2023)
The purpose of the study was to establish why drug abuse has become a challenge to society today more especially the Juveniles. The study will aim at achieving the following objectives: To examine how drug abuse affects juvenile growth in Kabale Municipality. To examine the causes of drug abuse among juveniles in Kabale Municipality. To find out the remedies for drug abuse in Kabale Municipality. The study adopted a case study research design, where quantitative and qualitative approaches were employed. The sample of the population taken included political leaders, development social workers police activist youth and the community at large were part of the study population. Data was collected using questionnaires, interview guides, and library sources for secondary data. From this stage, several findings were filed as expected and the following chapters followed with recommendations and conclusions.